How to measure the economic impacts of mega-events - the example of the World Economic Forum in Davos - Roland Scherer; Simone Strauf (European Regional Science Association (ERSA), 2003)
The number, diversity and popularity of events has increased in the recent years. The question of the concrete economic effects for the location and the surrounding region becomes therefore more and more important. Because every economic activity whether a public intervention or an economic action causes changes in the consumer demand. To measure the economic effects of events you can use different scientific methods. Using the traditional methodological approaches like the input-output-analysis, the cost-benefit analysis or the financial mathematics you can exclusively point out the monetary effects which are directly connected with the event. On the other hand the longterm intangible effects could only be included partially. However the ascertainment of the intangible and longterm effects like the meaning of competences and the learning of regions has become more and more important for the analysis of the spatial effects of mega-events in the recent years. The example of the Annual Meeting of the World Economic Forum in Davos shows how the direct as well as the indirect effects of events could be worked out based on the spatial incidence analysis. The incidence analysis is a kind of cost-benefit analysis which is especially suited for analysing the spatial effects of infrastructural facilities or the service of these facilities. Another advantage is that you can present the results relatively transparent and coherent. Strict-talken the incidence analysis is a systematic to the ?problem-related? and spatial order of accounting and statistical information. It considers the basic principles of economic impact analysis, especially focussing on the clearly spatial and textual correlation of the cash flows. In spite of certain methodological and theoretical deficits the spatial incidence analysis seems to be qualified for the presented analysis as a methodological basis. In the context of the the incidence analysis, the theoretical guidelines were adapted to the specific facts of the Annual Meeting of the World Economic Forum. The question of the direct and indirect effects of the World Economic Forum was pointed out as the center of the analysis. Considering the direct effects you focus on the receipts and expenditures which are directly connected with the realisation of the event. The indirect effects could be devided into the so called tangible and intangible effects. Tangible effects are measurable as indirect economic effects. These are the so called spill-over effects. The intangible effects could be explained as soft and mostly not quantifiable effects. Normally these effects are distinguished between image effects (positive and negative), infrastructure-, structure-, competence- and network effects. These effects often cause a clearly higher contribution to the development of an event location than the direct monetary amount to the regional national income. To analyse these effects we used a combination based on a demand-oriented and supply-oriented approach to calculate the whole transaction volume of the event. Spatially we differed between the effects concerning Davos itself, the region of Graubünden and the rest of Switzerland.
Keywords: 330